2019
DOI: 10.1038/s41401-019-0323-8
|View full text |Cite
|
Sign up to set email alerts
|

Metoprolol prevents neuronal dendrite remodeling in a canine model of chronic obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA) is closely associated with central nervous system diseases and could lead to autonomic nerve dysfunction, which is often seen in neurodegenerative diseases. Previous studies have shown that metoprolol prevents several chronic OSA-induced cardiovascular diseases through inhibiting autonomic nerve hyperactivity. It remains unclear whether chronic OSA can lead to dendritic remodeling in the brain, and whether metoprolol affects the dendritic remodeling. In this study we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The majority of evidence indicates that intermittent hypoxia, one of the most damaging effects of OSA, causes decreases in BDNF levels in animal models [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Fang et al studied the influence of CIH (chronic intermittent hypoxia) on neurodegeneration of the optic nerve in mice model, showing decreased BDNF levels.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of evidence indicates that intermittent hypoxia, one of the most damaging effects of OSA, causes decreases in BDNF levels in animal models [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Fang et al studied the influence of CIH (chronic intermittent hypoxia) on neurodegeneration of the optic nerve in mice model, showing decreased BDNF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical studies have shown that the insula consists of ventral anterior, dorsal anterior, and posterior lobe subregions previous study reported that neuronal activity between the dorsomedial prefrontal cortex and anterior insula is critical in emotion management techniques (Dörfel et al 2014). In an animal experiment, chronic hypoxia caused a signi cant reduction in the number, length, and crossover point of neuronal dendrites in the prefrontal cortex, ultimately causing neuronal remodeling (Yang et al 2020). According to rs-fMRI studies, structural and functional abnormalities in the mPFC of OSA patients are related to cognitive impairment (Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies show that OSAHS is complicated with COPD in about 10 % of patients, while 50 % of patients with moderate and severe COPD have OSAHS complication [12][13][14][15]. In recent years, with advancements in social economy, the incidence of COPD-OSAHS has significantly increased due to environmental pollution, smoking, obesity, and unbalanced diet.…”
Section: Discussionmentioning
confidence: 99%